2000
DOI: 10.1086/314240
|View full text |Cite
|
Sign up to set email alerts
|

The Stomatal Ontogeny and Structure of the Liassic Pteridosperm Sagenopteris (Caytoniales) from Hungary

Abstract: Stomatal ontogeny is often inferred but rarely documented for extinct fossil plants because it requires observations from young leaves that are rarely preserved as fossils. The discovery of several very young leaves of the Jurassic plant Sagenopteris (Caytoniales) in the Mecsek Mountains (southern Hungary) in a good state of preservation provides the opportunity for studying the stomatal ontogenesis of this genus. The specimens show perigenous anomocytic stomata. This feature confirms the evolutionarily high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 15 publications
1
19
0
2
Order By: Relevance
“…This type of patterning, coupled with Harris' (1976) observation of 'occasional monstrous stomata' in Mesozoic bennettites, strongly indicates that stomatal development is mesogenous or mesoperigenous rather than perigenous (this paper) Caytoniales* (Sagenopteris) Stomata anomocytic/stephanocytic; development incompletely known Stomata were scored as stephanocytic by Carpenter (2005). Sagenopteris stomata were described as anomocytic (Barbacka & Bόka, 2000), or with a ring of 10-15 small subsidiary cells (Barbacka et al, 2006). Barbacka & Bόka (2000) also showed some late stages of epidermal development, including linear cell files with some recently divided cells (lacking asymmetric divisions), and some recently divided GMCs; they tentatively concluded that development is perigenous, but more data are needed to confirm this observation Angiosperms (Fig.…”
Section: Gnetalesmentioning
confidence: 81%
See 1 more Smart Citation
“…This type of patterning, coupled with Harris' (1976) observation of 'occasional monstrous stomata' in Mesozoic bennettites, strongly indicates that stomatal development is mesogenous or mesoperigenous rather than perigenous (this paper) Caytoniales* (Sagenopteris) Stomata anomocytic/stephanocytic; development incompletely known Stomata were scored as stephanocytic by Carpenter (2005). Sagenopteris stomata were described as anomocytic (Barbacka & Bόka, 2000), or with a ring of 10-15 small subsidiary cells (Barbacka et al, 2006). Barbacka & Bόka (2000) also showed some late stages of epidermal development, including linear cell files with some recently divided cells (lacking asymmetric divisions), and some recently divided GMCs; they tentatively concluded that development is perigenous, but more data are needed to confirm this observation Angiosperms (Fig.…”
Section: Gnetalesmentioning
confidence: 81%
“…Sagenopteris stomata were described as anomocytic (Barbacka & Bόka, 2000), or with a ring of 10-15 small subsidiary cells (Barbacka et al, 2006). Barbacka & Bόka (2000) also showed some late stages of epidermal development, including linear cell files with some recently divided cells (lacking asymmetric divisions), and some recently divided GMCs; they tentatively concluded that development is perigenous, but more data are needed to confirm this observation Angiosperms (Fig. 7) Stomata both anomocytic and paracytic; possibly ancestrally paracytic and mesoperigenous Many types have been reported (e.g.…”
Section: Gnetalesmentioning
confidence: 99%
“…Studies of fossil stomata and their associated subsidiary and neighboring cells can provide insights into the origin and evolution of developmental pathways of the stomatal complex (Barbacka and Bóka, 2000;Barclay et al, 2007;Bomfleur and Kerp, 2010;Rudall et al, 2013). This is more than just an academic exercise as a deeper understanding of the origin, evolution, and diversity of stomatal developmental pathways in both extant and extinct lineages underpins genetic engineering programs for altered stomatal conductance, assimilation rates, and leaf cooling capacities in modern crop plants.…”
Section: Developmental Insights From the Fossil Stomatal Complexmentioning
confidence: 99%
“…This composite plant is the only member of the order, which is thought to be a derived and isolated group of seed ferns. Some authors have suggested that it is a possible sister-group of the angiosperms (Doyle and Hickey 1976;Donoghue 1986, 1992;Barbacka and Boka 2000), but we reject this assertion by placing it in the superclass Medullosopsae.…”
Section: Notes On the Figuresmentioning
confidence: 56%